Haemodynamic effects of prenalterol in patients with coronary heart disease. Issue 2 (February 1980) - Hutton, I; Murray, R G; Boyes, R N; Rae, A P; Hillis, W S
Abstract : The haemodynamic effects of prenalterol, a new selective beta-1 adrenoreceptor agonist, have been studied in patients with coronary heart disease. The drug was administered intravenously in a dosage of 0.5 to 2.5 micrograms/kg body weight to 20 patients undergoing coronary angiography and to 10 patients with a recent myocardial infarction, who had clinical evidence of left ventricular dysfunction. Left ventricular performance was enhanced in both groups of patients–left ventricular dP/dt (max) increased by 33 per cent and the systolic time intervals, pre-ejection period, and the ratio of pre-ejection period and left ventricular ejection shortened by 28 and 21 per cent, respectively. Cardiac output and stroke volume increased with no change in heart rate nor in left ventricular filling pressure. These results indicate that prenalterol enhances the contractile state of the myocardium without altering heart rate, and suggest that prenalterol could be of value in the management of patients with coronary heart disease, who have impaired left ventricular function.